Aphasia assessment: impact of material on naming performance - Fonseca, José; Miranda, Filipa de; Leal, Gabriela; Melo, Teresa Pinho e; Martins, Isabel Pavão (Arquivos de neuro-psiquiatria, 2021)
ABSTRACT Background: Naming and lexical retrieval difficulties are common symptoms of aphasia. Naming abilities are usually evaluated by means of real objects or pictures or line drawings that are printed. Objective: The aim of this study was to investigate whether the ability to name objects among individuals with aphasia is influenced by the dimensions of the visual stimuli and to understand whether the order of presentation of the stimuli, number of years of education and length of time post-onset are involved in the success of naming. Methods: The naming abilities of healthy controls and patients with acute or chronic aphasia due to stroke were assessed through presentation of two sets of 24 stimuli consisting of real objects and color photographs of the same objects presented on a screen. The results obtained under these two conditions were compared by means of within-subject paired ANOVA, controlling for presentation order. Results: 40 patients (62.4 ± 17.3 years old; 70% females; mean education level of 8.5 ± 5.3 years; and 60% evaluated within the first eight days after stroke) and 50 controls that were age, gender and education-matched were included. Object naming was significantly better than naming color photographs among the patients ( p = 0.001), but no differences were observed among the controls. Age, education, length of time post-onset and presentation sequence did not have any impact on naming performance. Conclusion: These results suggest that use of digital color photographs for naming objects in assessment of aphasia may be associated with lower naming performance, compared with use of real objects. This needs to be taken into account when different forms of stimuli are presented in sequential aphasia evaluations.